TURISMO DE BASE COMUNITÁRIA COMO ESTRATÉGIA DE DESENVOLVIMENTO LOCAL NO PROJETO DE ASSENTAMENTO ÁRVORES VERDES, BREJO – MA - ROCHA, Perla do Nascimento (2025)
Community-based tourism (TBC) is a promising alternative for local development in rural communities, integrating strategies for income generation and social inclusion. In the state of Maranhão, this modality is still little explored, but it has the potential to be consolidated in agrarian reform settlements, such as the Árvores Verdes Settlement Project (PA), located in the municipality of Brejo. This study investigates how CBT can contribute to economic, social and environmental development, proposing sustainable tourism practices adapted to local characteristics. The methodology adopted is based on the geographic categories of territory and territoriality, associated with bibliographical analysis and empirical survey. The research prioritizes the characterization of the use and occupation of the territory, the identification of natural and cultural tourism potential, and the formulation of strategies for the implementation of community tourism. The territory of the PA in question is notable for the presence of the Parnaíba River and the Comprida, Fartura and Escalvado lakes, natural resources that enrich the tourism potential of the locality. The results show that, although the settlement has characteristics that are favorable to the development of TBC, the lack of structured public policies and training initiatives limits the effective involvement of settlers in tourism activities. These challenges reinforce the need for participatory planning that integrates the community in the decision-making process and promotes the appreciation of local potential. It is therefore concluded that TBC, when implemented in an inclusive and sustainable manner, can act as a vector for social and economic transformation, diversifying the sources of income of rural communities and promoting environmental conservation. The research reaffirms the importance of community leadership as a central element in consolidating tourism as a viable alternative to traditional agricultural practices, contributing to improving the quality of life in the PA Árvores Verdes.